Dogwood Hill - Woods, Sherryl (Don Mills, Ontario : Mira, 2015)
When former pro football quarterback Aidan Mitchell comes to Chesapeake Shores to take a high school coaching job, he's embraced by the town--especially the O'Briens. But Aidan has a secret that could alter all their lives.
Keywords: Secrets -- Fiction; Football coaches -- Fiction; Ex-football players -- Fiction; Betrayal -- Fiction; Man-woman relationships -- Fiction; Love stories